AZ EU 2021-2027-ES TÖBBÉVES PÉNZÜGYI KERETÉNEK HATÁSA A VIDÉKFEJLESZTÉSRE - Koponicsné Györke, Diána (Közép-Európai Közlemények, 2020)
The adoption of the new multiannual financial framework for the period 2021-2027 is one of the most important questions in the EU nowadays. It always belongs to the most difficult and time-consuming decisions the member states have to make. Such a decision should represent several interest like the net contributor and net beneficiary states’ aims, the willingness of the European Commission and the European Parliament to make the cooperation among the countries deeper and to extend the cooperation to new policy areas too. The EU’s long term multiannual financial framework (MFF) influences and somehow defines the next years’ yearly budget and the benefits the member states can receive from the common budget of the EU as well. The main spending numbers represents the importance of the different policy areas as the EU provides resources for the topics which will be in focus in the next seven years. The decision about the new MMF is more complicated than the earlier ones. As a result of the Brexit there will be a gap in the common budget. As at the beginning of the MFF negotiations the way and the exact date of the Brexit was not clear the whole process became less transparent and predictable. On the other hand, the EU planes to provide significantly more money to new priorities and goals like border security, competitiveness or foreign policy. It means that the two traditional beneficiary policy areas’ (the CAP and the Cohesion spending) share should decrease within the common budget. This study examines the effects of this decrease on the CAP 2nd pillar, rural development.